LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS PENGARUHNYA TERHADAP KINERJA NILAI PERUSAHAAN PARIWISATA, RESTORAN DAN HOTEL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022 - Friyanto; Sudarjo; Selfiah (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2026)
This study aims to determine and analyze Liquidity, Solvency and Profitability Growth partially and simultaneously which have a significant effect on Company Value in the Tourism, Restaurant and Hotel sub-sectors listed on the Indonesia Stock Exchange for the 2019–2022 period, and also to find out among the variables Liquidity, Solvability and Profitability, which variable has the most dominant influence on the value of tourism companies, restaurants and hotels listed on the Indonesia Stock Exchange for the 2019–2022 period. In this study the approach used is a quantitative approach. The population in this study are tourism companies, restaurants and hotels listed on the Indonesia Stock Exchange for the 2019–2022 period, totaling 46 companies. While the sample used was a purposive sampling technique with certain criteria that had been determined by previous researchers so that a final sample of 10 companies was obtained multiplied by a period of 4 years, namely during the 2019-2022 research period, 40 research sample data were obtained. and the results are processed with the help of SPSS 25.0. The results of the study show that testing the independent variables, namely the variables Liquidity Current Ratio (X1), Solvability Debt to Equity Ratio (X2) and Profitability Return on Assets (X3) simultaneously prove to have a significant effect on the Company Value Price to Book Value (PBV) (Y) and has a positive and significant influence. While from the partial test, among the three independent variables consisting of Liquidity, Solvency and Profitability it turns out that the most dominant influence on Firm Value is the Profitability Ratio